Left atrial myxoma causing near-total mitral valve obstruction - Chan, En Ze; Chang, Chee Yik (Wiley, 2023)
Cardiac myxomas are the most common primary cardiac tumors in adults, with the left atrium being the most frequently affected. Echocardiography is the diagnostic modality of choice. The most effective treatment for cardiac myxomas is surgical excision.